Analisis Penerapan SAK EMKM pada UMKM di Kota Kaliwungu: Perspektif Teori Sinyal - Diella Islamy Rahma Putri; Muhammad Ja’far Shodiq (BADAN PENERBIT STIEPARI PRESS, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have a very important role in the Indonesian economy. MSMEs not only contribute greatly to gross domestic product (GDP), but also become absorbers of labor in various sectors. The existence of MSMEs helps drive the local economy, reduce the unemployment rate and improve community welfare. The purpose of this study is to find out how the level of implementation of the accounting recording system, educational background and socialization affects the implementation of SAK EMKM in Kaliwungu City. The type of sample used in this study was 93 samples of respondents or MSME actors in Kaliwungu City. This data was obtained from questionnaires that were distributed both offline and online, then this data was processed using the SPSS application with sample collection techniques using the purposive sampling method. The results of this study show that the variable level of implementation of the accounting recording system has a positive and significant effect on the implementation of SAK EMKM, educational background has a positive and significant effect on the implementation of SAK EMKM, and socialization has no effect on the implementation of SAK EMKM.